SISTEM PENGISIAN SALDO KWH METER DIGITAL PRABAYAR JARAK JAUH BERBASIS SMS GATEWAY - Zoel Fachri; Nasrullah (Politeknik Aceh, 2015)
As the development of the current technology all the things already made easy with State of the art equipment as well as prepaid electricity kWh meter functionality so users can power savings and not the onset of delinquency, this is beneficial Power of State parties (PLN) but complicates the user (consumer) in filling the power balance prepaid charging process manually via keypad. Balance SMS-based charging system will simplify the user in filling out the balance of electricity prabayarnya those in homes through official place of purchase electric token. The control system developed by mikrokontroller programming and communication interface which is connected with a digital meter prepaid and computers as well as mobile devices can run well but still the need for synchronization with the PLN to get optimal results.